Analysis of the Molecular Structure of Lipase-Dependent Chaperone from Ralstonia pickettii Strain BK6 - Muhamad Azwar Syah; Sri Ambardini; Jamili Jamili; Muzuni Muzuni; Darul Trisandy (Jurnal Biodjati, 2024)
Several biotechnology industries are exploring the characteristics of lipase-dependent chaperones due to their distinctive biochemical traits. This study aimed to employ bioinformatics to analyze the molecular structure of Ralstonia picketii BK6's lipase-dependent chaperon (LipRM). The sequence mapping and amino acid distribution were examined using BioEdit (version 7.0.9.1). SignalP 5.0 and Interpro are employed for signal peptide detection, whereas Swiss-Model and VMD 1.9.2 are used for molecular dynamics modelling. The results showed that the Shine-Dalgarno sequence was discovered in the LipRM promoter, seven nucleotides upstream of the initiation codon (AUG) with the 5'-AGGAGA-3', and has a terminator region that facilitates the formation of a secondary structure. The protein's 3D structure prediction results indicate differences in the alpha helix chains (residues 166-174 and 254-271) between LipRM and the reference lipase. LipRM's molecular structure comprises a detachable signal peptide, and with variations in helix alpha chain conformation and ligand geometry.